Three tests of the Vulnerability-Stress-Adaptation Model: Independent prediction, mediation, and generalizability - Ross, Jaclyn M.; Nguyen, Teresa P.; Karney, Benjamin R.; Bradbury, Thomas N. (Frontiers in Psychology, 2022)
Objective: Efforts to understand why some marriages thrive while others falter are (a) not well integrated conceptually and (b) rely heavily on data collected from White middle-class samples. The Vulnerability-Stress-Adaptation Model (VSA; Karney & Bradbury, 1995) is used here to integrate prior efforts and is tested using data collected from couples living with low incomes. Background: The VSA Model assumes (a) that enduring vulnerabilities, stress, and couple communication account for unique variance in relationship satisfaction, (b) that communication mediates the effects of vulnerabilities and stress on satisfaction, and (c) that the predictors of satisfaction generalize across socioeconomic levels. To date, these assumptions remain untested. Method: With 388 couples from diverse backgrounds (88% Black or Hispanic), we used latent variable structural equation models to examine enduring vulnerabilities, chronic stress, and observed communication as predictors of 4-wave, 27-month satisfaction trajectories, first as main effects and then interacting with a validated 10-item index of sociodemographic risk. Results: (a) The three variable sets independently predict satisfaction trajectories; (b) couple communication does not mediate the effects of enduring vulnerabilities or stress on satisfaction; and (c) in 19% of tests, effects were stronger among couples with higher sociodemographic risk. Conclusion: Effects of established predictor domains on satisfaction replicate in a diverse sample of newlywed couples, and most findings generalize across levels of sociodemographic risk. The failure of couple communication to mediate effects of enduring personal vulnerabilities and stress raises new questions about how these two domains undermine committed partnerships.